Participation of the Basque Country in the Spanish Civil War (1936-1939) - A. Landabaso Angulo (Ибероамериканские тетради)
The most bloody war in XX century in Europe is Civil War in Spain in 1936-1939. The end of this war according to francist terminology feels to March 1939, when «victorous» army of general-insurgent F. Franco entered Madrid. But upon republican part of Spain, end of the Civil War in one version is 1967, when the last regular army in the Oran valley (southern Catalonia) laid down its arms. According to the other version, end of the Civil War matches with abdication of head of the Republic in exile (L. ). Asha) is 1971. Until the present, Spain (according to surveys, more than 53.6 % of its citizens) celebrates key dates of the Spanish Republic like Day of the proclamation of the Republic, all the holidays of the Republic, uses the symbols of the Republic, for example, its tricolor. The biggest part of social organizations, registeres in Spanish Ministry of Internal Affairs, are of social-political orientation (veteran organizations, trade unions, political parties, even various discussion clubs belong to the Republican orientation). Seven of 17 Spanish autonomous regions are majority-Republican, but not monarchist by origin. The largest of them I will name: Catalonia, Basque Country, Navarra, Asturias, Andaluzia, Murcia.The article is dedicated to little-known, almost not studied events, obscure even for spanish expert society, linked with struggle on the Northern front - the key phase of the Spanish Civil war. It discloses decisive moments of this struggle, after which the Civil War should be treated as finished, with negative result for the Republic.Nothing is forgotten, no one is forgotten. Today, after more than 80 years after the tragic evens, the main resume, evident for each researcher of the Civil War in Spain is that there could be no winners or losers. Everyone suffers a defeat.